(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
Firstly, a typical slope on Liu-An highway was selected as the research object. Then, based on the Sarma algorithm and considering the influence factors such as inhomogeneous boundary conditions, water content and reinforcement Angle, A slope stability analysis system based on the improved Sarma algorithm is developed to build an engineering geological model and a remote intelligent monitoring system platform for the slope. On this basis, we select the slope of typical road sections for remote monitoring and pre-warning. ArcGIS technology is used to carry out difference analysis of monitoring data, realize GIS 3D visualization, and verify the 3D visualization monitoring effect of the system. The results show that the system is stable and reliable. The range and precision meet the specification requirements, and can effectively realize the 3D visualization monitoring of highway slope. It can also realize four-level pre-warning, which lays a foundation for the long-term safe operation of highway.